Effect of Early Mobilization on Intestinal Peristaltic Recovery As Prevention of Paralytic Ileus in Post Cesarean Section Patients - fania khoirunnisa; Nailil Muna; Ika Tristanti; Ashri Rahmawati; Purbowati (Masters Program in Public Health, 2025)
Background: The majority of cesarean section deliveries use spinal anesthesia which can have an effect on the deterioration of the gastrointestinal system so that intestinal peristalsis becomes slow. Slow intestinal peristaltic function leads to difficulty defecation and prolongs the day of treatment, in some cases can increase the risk of paralytic ileus. To prevent the risk of complications, intervention can be carried out in postoperative cesarean section patients with early mobilization. This study aims to determine the effect of early mobilization on intestinal peristaltic recovery in post- cesarean section patients. Subjects and Method: This was a quasy experiment conducted at Islamic Hospital in Demak, Central Java, from July to December 2024. A sample of 58 post-cesarean section mothers was selected using purposive sampling and divided into two groups. Assessment of intestinal peristaltic variables through auscultation examination with a stethoscope and early mobilization using observation sheet instruments. Intestinal peristaltic recovery between two groups were examined logistic regression. Results: There was a difference in intestinal peristaltic recovery in post- cesarean section patients between the intervention group and the control group (p=0.000) with the mean value of intestinal peristalsis in the intervention group of 25.45 (SD=6.07) and in the control group of 11.38 (SD=7.69). Patients who were given early mobilization had a 4.48 times faster chance of recovery of intestinal peristalsis. Conclusion: Early mobilization had a positive impact on the recovery of intestinal peristaltic (p<0.05). Health workers should not only provide education, but also assistance in the implement-tation of early mobilization, especially in the first 24 hours post- cesarean section.Keywords: early mobilization, intestinal peristaltics, post cesarean section.